Ответы и объяснения

2013-11-07T17:53:14+04:00
#4 (1)
( \sqrt{27}-2 \sqrt{3}- \sqrt{2})*( \sqrt{2}+ \sqrt{3})= ( 3\sqrt{3}-2 \sqrt{3}- \sqrt{2})*( \sqrt{2}+ \sqrt{3})=( \sqrt{3}- \sqrt{2})*( \sqrt{2}+ \sqrt{3})=3-2=1
#5 (1)
 \frac{a-9}{ \sqrt{a}+3}= \frac{ (\sqrt{a}-3 )(\sqrt{a}+3)  }{ \sqrt{a}+3}= \sqrt{a}-3
#6 
(2^3-3)*(7+4^3)/1^12+3= 7^12+1^576-21-3^48/1^12+3=2^3+3/2^3+3=1
#7 (3)
u= \sqrt{6} y= \sqrt{24} 
 2u^{2}+5uy-3y^{2}=2*6+5*12-3*24=12+60-72=0
#8
 (x-2)^{2}* \frac{1}{ \sqrt{4-4x+x^2} }=(x-2)^{2}* \frac{1}{ \sqrt{(x-2)} }= \frac{(x-2)^2}{ \sqrt{(x-2)} }=1
про решение восьмого - не уверен